Community-Based Education Practices in Resettlement: Insights from the Blacksburg Refugee Partnership - Keyel, Jared A (Migration Letters, 2021)
Education is a key component of the processes refugees undertake to (re)establish their lives in their new communities. In many cases too, displaced individuals have had interruptions in their education paths. In the United States context, nonprofit and community organizations provide essential services to supplement publicly funded resettlement and educational programs. The Blacksburg Refugee Partnership (BRP) has been filling service provision gaps in Southwest Virginia for a group of resettled refugee households since late 2016. BRP provides tutoring, English as a Second Language (ESL) training, and summer supplemental programming. Based upon an interview with BRP’s Education Coordinators and a survey of leaders and volunteers in September 2018, this article explores the organization’s work, connecting it to challenges and opportunities similar education initiatives encounter. I organize research results around three primary themes: the benefits of resettlement in a “college town” and the importance of leveraging university resources; the complexity of volunteer-led programming; and the need for comprehensive services to facilitate students’ education. I conclude by sketching the implications of this case for other educational initiatives serving refugees.